Trabeculectomy With Mitomycin C or Ahmed Valve Implantation in Eyes With Uveitic Glaucoma. Issue 8 (October 2015) - Bettis, Daniel I.; Morshedi, Richard G.; Chaya, Craig; Goldsmith, Jason; Crandall, Alan; Zabriskie, Norm
<x xml:space="preserve">Abstract</x> Purpose: To report and compare the results of trabeculectomy with mitomycin C (MMC) and Ahmed valve implantation in the management of uveitic glaucoma. Patients and Methods: The records of 41 eyes of 29 patients who underwent trabeculectomy with MMC or Ahmed valve implantation for uveitic glaucoma were retrospectively reviewed. Seventeen eyes underwent trabeculectomy with MMC, and 24 eyes underwent Ahmed valve implantation. Outcomes included postoperative intraocular pressure (IOP), percent reduction from preoperative IOP, postoperative number of medications, time to failure, and complications. Results: Mean follow-up was 21.2 months in the trabeculectomy group and 23.8 months in the valve group (P=0.06). Mean IOP was reduced from 29.2 to 18.4 mm Hg in the trabeculectomy group (31.3%), compared with a reduction from 33.4 to 15.5 mm Hg in the Ahmed valve group (42.7%, P=0.53). Postoperatively, 1.76 medications were used in the trabeculectomy group, compared with 1.83 medications in the Ahmed valve group (P=0.89). Cumulative success at 1 year was 66.7% in the trabeculectomy group, compared with 100% in the Ahmed valve group (P=0.02). Mean time to failure was 8.36 months with trabeculectomy, and 21.8 months with Ahmed valve (P=0.02). Complications in both groups were typically rare and self-limited, with recurrent inflammation being most common. Conclusions: Although both trabeculectomy with MMC and Ahmed valve implantation are reasonable surgical options in the management of uncontrolled uveitic glaucoma, Ahmed valve implantation was associated with higher cumulative success rate at 1 year and a longer mean time to failure.